The teaching experience of Mario de Andrade at the Arts Institute of the University of the Federal District ― RJ (1938-1939) (Revista de Ensino em Artes, Moda e Design, 2021)
This article reflects on the teaching experience of Mario de Andrade, when the renowned poet assumed the chair of Philosophy and History of Art at the Arts Institute of the University of the Federal District (RJ) ― IA / UDF. This university was created by Anísio Teixeira in 1935 in the City of Rio de Janeiro, at the time Capital Federal. The UDF was a different institution because its main objective was to train teachers for different areas of knowledge. There were many struggles faced by this institution that had a short existence (1935 to 1939). In this institution, in addition to Mário de Andrade, eminent figures of Brazilian modernist art also served as teachers. Thus, the main objective of this research is to understand what were the contributions of Mario de Andrade as a professor at the UDF Institute of Arts for the training of teachers of Arts (Drawing and Painting) of that institution. The theoretical framework that guides the reflections of this research is based on the works of the following authors: Bomeny (2012), Coutinho (2002), Lopes (2006, 2009) and Mendonça (2002). The methodology consisted of documentary analysis of the collections of the following institutions: UFRJ Education and Society Program of Studies and Documentation; Portinari Project of PUC-Rio and Digital Library of the National Library. The analysis of the sources allowed to confirm the modernist character of the teaching of the UDF Institute of Arts and that Mario de Andrade intended to awaken in his students an artistic awareness from the development of a personal technique, without limiting the artist to rigidly established standards.Keywords: Mário de Andrade; Teacher training; Modern Art.
Keywords: Mário de Andrade; Teacher training; Modern Art